First isolation of Clostridium indolis in a patient with chronic osteitis: a case report and literature review of human infections related to Clostridium saccharolyticum group species. (December 2016) - Lotte, Romain; Lotte, Laurène; Bouvet, Philippe; Degand, Nicolas; Bal, Antonin; Carles, Michel; de Dompsure, Regis Bernard; Popoff, Michel-Robert; Ruimy, Raymond
Abstract: Clostridium indolis is an anaerobic spore-forming Gram-positive bacillus belonging to the Clostridium saccharolyticum group. Its clinical significance in human remains poorly known. We describe the first case of osteitis related to C. indolis, identified by MALDI-TOF mass spectrometry and provide a literature review of human infections related to C. saccharolyticum group species.